Strategi Menyusun Manajemen Keuangan dalam Lembaga Pendidikan Islam - Inaldi, Irani Surya Kartini; Rindaningsih, Ida (Jurnal Kependidikan Islam, 2024)
Educational financial management plays a crucial role in Islamic Education Institutions. Therefore, a strategy is necessary for the survival and development of these institutions. The relationship between educational institutions and financial management is inseparable. This research employs the library research method and gathers data from Mendeley, Publish or Perish, and Google Scholar applications. During the research process, researchers will analyse case studies, implementation examples, and financial reports from previous educational institutions. They will also analyse policies and regulations related to financial management in educational institutions that are implemented in various settings. The aim of this research is to provide a solution for achieving the goals of Islamic Education Institutions by improving their financial management system. The research findings indicate that effective educational financial management strategies are not only based on the principles of planning, organizing, actuating, and controlling, but also require human resources with both professional competence and a correct understanding and implementation of Islamic law, from an Islamic perspective. It is important to note that Islamic rules are more intricate than scientific discoveries.